LEGAL CERTAINTY AND LAND RIGHTS CONFLICT: A NORMATIVE-EMPIRICAL STUDY OF SULTANATE LAND UTILIZATION IN YOGYAKARTA - Wah Idna Aminudin; Muhammad Farid Alwajdi (Universitas Syiah Kuala, 2026)
This study examines the legal issues surrounding land use rights in the Special Region of Yogyakarta, focusing on the tension between regional autonomy over Sultanate land and national agrarian principles. The problem raised centers on a significant legal gap at Gesing Beach, where residents utilized land for decades without formal serat kekancingan permits. This administrative void created legal uncertainty and vertical conflict when the government reclaimed the land for a Fish Landing Base (PPI) project, resulting in the loss of local livelihoods. Employing a normative-empirical method, this article analyzes legal norms, specifically Regional Regulation No. 1 of 2017, alongside qualitative data gathered through interviews and observations. The findings indicate that the principles governing Sultanate land have not been fully or consistently applied, leading to poorly established legal relationships. This study reveals that state developmental interests often sidelined individual rights, with mediation efforts perceived as inadequate in addressing community demands for fair compensation. This article contributes to understand on how